Population Trends of Quails in North America - Kevin E. Church; John R Sauer; Sam Droege (National Quail Symposium Proceedings, 2017)
We used North American Breeding Bird Survey data (1966-91) to estimate distribution, relative abundance, and population trends of quails. Population trends in grassland/shrub birds sympatric with northern bobwhite (Colinus virginianus) were also examined. Northern bobwhite and scaled quail (Callipepl,a squamata) populations have declined since 1966. Rates of decline for these quails have increased during the past decade. California quail (C. califomica), Gambel's quail (C. gambelii), and mountain quail (Oreortyx pictus) populations have been stable over the long-term (1966-91). However, the short-term (1982-91) trend for California quail is positive, whereas Gambel's quail appear to be declining. Patterns in trends indicate similar factors may be negatively affecting breeding populations of grassland/shrub birds throughout the bobwhite's range. We discuss plausible hypotheses to explain population trends and recommend future action.
Keywords: abundance; Breeding Bird Survey; California quail; distribution; Gambel& #x27; s quail; mountain quail; North America; northern bobwhite; population trends; quail; scaled quail